AB1011 Clinical trial of intravenous infusion of fucosylated bone marrow mesenchymal stem cells in patients with osteoporosis. (12th June 2018) - Lozano-Rivas, N.; Linares, L.F.; Marras-Fernandez-Cid, C.; Garcia-Hernandez, A.M.; Algueró, M.D.C.; Iniesta, F.; Sanchez-Salinas, D.; López-Lucas, M.D.; Rodriguez-Valiente, M.; Cabañas, V.; García-Bernal, D.; Molina, M.D.M.; et al.
Abstract : Background: Osteoporosis (OP) is a systemic bone disease characterised by decreased bone mass and deterioration of bone microarchitecture with increased brittleness and fracture risk. It associates high morbidity and mortality for patients and has a high impact on health expenditure. Bone marrow stromal mesenchymal stem cells (BM-MSC) give rise to osteoprogenitor cells and osteoblasts and influence bone homeostasis. However after their intravenous (i/v) infusion their osteotropism is limited. Our group has demonstrated that the exofucosylation of the CD44 membrane antigen in MSC improves their homing to bone tissue and that the infusion of these cells is safe in a murine model. Objectives: To evaluate the safety of i/v infusion of fucosylated BM-MSC in patients with OP, and secondarily assess their ability to improve the course of the disease Methods: 10 women between 50 and 75 years old diagnosed with osteoporosis with a low impact fracture will be included and treated i/v with autologous fucosylated BM-MSC. The first 4 patients were treated with a dose of 2 × 10 6 cells/kg body weight and the other 6 with 5 × 10 6 cells/kg body weight. A 24 month follow-up will be conducted to evaluate the rate of severe and non-serious adverse events and secondary endpoints (decreased fracture rate, pain scores, functional status and quality of life, biochemical indexes of bone metabolism, quantitative computed tomography for morphometric and mechanical analysis of bone quality, densitometry, and histomorphometry Results: Seven patients have been recruited to date. Two left the study for lack of cell proliferation and appearance of a complex form in karyotype during the cell culture, respectively. The first 4 patients were successfully infused, and after a median follow-up of 3 months no related adverse effects have been observed, no new osteoporotic fractures have appeared, and the analogue pain scale score (EVA) shows a tendency to decrease of pain in 3 of the 4 patients. Conclusions: Our preliminary data indicate that clinical and GMP-grade production of BM-MSC is feasible. We have not observed any short-term adverse effects associated with treatment in infused patients. Disclosure of Interest: None declared